Investment Motivation, Technological Advancement, and Financial Literacy on Investment Interest in the Capital Market - Setyawati, Amelia (PT. EQUATOR SINAR AKADEMIA, 2025)
The study seeks to investigate how factors such as investor enthusiasm for investments, innovations in technology, and knowledge about finance influence people's inclination towards participating in stock trading markets. The study employs this quantitative methodology by gathering initial information through questionnaires. A targeted selection method was employed for choosing the study participants. The research gathered data from over 130 participants across various beginner stock investor forums located in Eastern Indonesia. This study employed multivariate analysis through linear regression techniques. Investment incentives influence investor engagement within financial markets. Technological advancements significantly influence investor enthusiasm. Partially, financial literacy influences investment enthusiasm significantly